Pola Asuh Orang Tua terhadap Motivasi Belajar Siswa di Sekolah Dasar - Afriani, Riska; Ain, Siti Quratul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Most of the students' inspiration lies in the upbringing of their parents. Because parenting is controlled in giving a positive impact on children. The purpose of this study was to find out about parenting styles and suggestions for inspiring learning for elementary school students. In addition, it also tries to find out what kind of parenting style is most influential according to learning inspiration. The method used is qualitative with the investigation of information used is an elucidating examination. The object of this research is grade 5 and 6 SD Kec. Siak. The information sorting strategy used is perception, meetings, and archives. The results showed that there were differences in the parenting style applied by the guardians. A more equitable parenting style is applied by the guardians, following a tyrannical and tolerant parenting pattern. 4 guardians with popularity-based parenting, 1 parent with dictatorial parenting, and 1 parent with soft parenting. Students with tyrannical upbringing and the majority have good and sufficient inspiration to learn. Meanwhile, students with tolerant parenting are less inspired. This study concludes that parental care and support affect student learning inspiration. There are four types of parenting found, namely tolerance, sound-based, legitimate, and neglected. The results obtained make it clear that voice-based parenting is the most productive parenting style compared to other parenting designs to help inspire learning.